PCR Assay for Identification of Histoplasma capsulatum Based on the Nucleotide Sequence of the M Antigen - Guedes, Herbert Leonel de Matos (American Society for Microbiology, 2003)
The major diagnostic antigens of Histoplasma capsulatum var. capsulatum are the H and M antigens, pluripotent glycoproteins that elicit both humoral and T-cell-mediated immune responses. The gene encoding the M antigen has previously been sequenced, and its sequence has significant overall homology to those of the genes for fungal catalases. Regions of the M-antigen gene with little or no homology were used to design four oligonucleotide sequences for application in the PCR detection and identification of H. capsulatum var. capsulatum. The PCR correctly identified the 31 H. capsulatum var. capsulatum strains isolated from human, animal, and soil specimens and 1 H. capsulatum var. duboisii isolate. PCR products of 111 and 279 bp were amplified with primers Msp1F-Msp1R and Msp2F-Msp2R, respectively. No amplification product was obtained from DNA extracted from an H. capsulatum var. farciminosum isolate. The specificity of the PCR with the M-antigen-derived primers was confirmed by the total absence of amplification products when genomic DNA from Paracoccidioides brasiliensis, Candida spp., Sporothrix schenckii, Cryptococcus neoformans, Blastomyces dermatitidis, Coccidioides immitis, Aspergillus niger, and Aspergillus fumigatus were applied in the reaction. This rapid, sensitive, and specific assay provides a way to identify typical and atypical isolates of H. capsulatum var. capsulatum.